Dialogic Feed-Forward in Assessment: Pivotal to Learning but not Unproblematic - Jennifer Hill; Harry West (Teaching & Learning Inquiry: The ISSOTL Journal, 2022)
A key debate in higher education is how assessment and feedback can be constructed to maximize opportunities for meaningful student learning. In this paper, we explore how a learning-focused model of feedback, teacher-student dialogic feed-forward, is enacted in practice, exposing many affordances but also some challenges. Adopting a small-scale intensive approach, we trace the learning journeys of four students through a second-year undergraduate unit at a British university and on into their third and final year of study, accessing verbal testimony, teacher written comments on draft and final summative coursework, and student performance within and beyond the unit. We present in-depth student responses, understanding, behaviours, and achievement with respect to the feed-forward dialogue, revealing the subtleties of their reactions. Our findings evidence the transformative power of assessment dialogue on student learning for a range of achievers. Dialogic feed-forward can act as a pivotal moment in learning, where students reflect on their work, judge their standards against criteria, and co-create positive actions for improvement. Students develop cognitively, meta-cognitively, and affectively, becoming more comfortable with challenge and more productive in their learning. We conclude by widening our frame of reference to problematize dialogic feed-forward within current debates about higher education pedagogy.